Weather effects on birds of different size are mediated by long‐term climate and vegetation type in endangered temperate woodlands. (12th December 2018) - Lindenmayer, David B.; Lane, Peter; Crane, Mason; Florance, Daniel; Foster, Claire N.; Ikin, Karen; Michael, Damian; Sato, Chloe F.; Scheele, Ben C.; Westgate, Martin J.
Abstract: Species occurrence is influenced by a range of factors including habitat attributes, climate, weather, and human landscape modification. These drivers are likely to interact, but their effects are frequently quantified independently. Here, we report the results of a 13‐year study of temperate woodland birds in south‐eastern Australia to quantify how different‐sized birds respond to the interacting effects of: (a) short‐term weather (rainfall and temperature in the 12 months preceding our surveys), (b) long‐term climate (average rainfall and maximum and minimum temperatures over the period 1970–2014), and (c) broad structural forms of vegetation (old‐growth woodland, regrowth woodland, and restoration plantings). We uncovered significant interactions between bird body size, vegetation type, climate, and weather. High short‐term rainfall was associated with decreased occurrence of large birds in old‐growth and regrowth woodland, but not in restoration plantings. Conversely, small bird occurrence peaked in wet years, but this effect was most pronounced in locations with a history of high rainfall, and was actually reversed (peak occurrence in dry years) in restoration plantings in dry climates. The occurrence of small birds was depressed—and large birds elevated—in hot years, except in restoration plantings which supported few large birds under these circumstances. Our investigation suggests that different mechanisms may underpin contrasting responses of small and large birds to the interacting effects of climate, weather, and vegetation type. A diversity of vegetation cover is needed across a landscape to promote the occurrence of different‐sized bird species in agriculture‐dominated landscapes, particularly under variable weather conditions. Climate change is predicted to lead to widespread drying of our study region, and restoration plantings—especially currently climatically wet areas—may become critically important for conserving bird species, particularly small‐bodied taxa. Abstract : Many factors including climate, short‐term weather and habitat can influence the distribution and abundance of biodiversity. The effects of these factors are often studied independently. Yet it is increasingly clear that many of these drivers interact with one another. In this paper for Global Change Biology, we explicitly study the interactions of long‐term climate, short‐term weather, habitat availability and life‐history attributes on bird biodiversity.